Jóvenes Actores Estratégicos del Desarrollo :análisis de la política pública de juventud. - Villavicencio Vaca, Carlos Daniel (2016)
The formulation of public policies in our country presents several challenges referring to the participation of young people with rights and the effort to articulate their voices, expectations, needs and their proposals in government policies to consolidate a constitutional vision of the Ecuador as a nation and youth as strategic actors of development. In this paper we propose to identify how communication becomes a tool to recognize the social causes of young people and how communicative exercise contributes the construction of young`s citizenship from the participation. We approach to one of the many youth manifestations. The theme for analysis will be marijuana`s or cannabis legalization and communicative exercise to influence socially in decriminalization of consumption and self-cultivation as social alternative to the drug phenomenon in Ecuador and specifically in Quito.